La crisis educativa en el Perú: cinco hipótesis explicativas - Alvarado Oyarce, Otoniel (2010)
In this essay, the author proposes five work hypotheses, properly adjusted in their epistemological categories, which deal with the poor quality of public education. Although the author recognizes some partial achievements, he assumes a critica! position towards different governments' performance, as they have neglected or abandoned some actions of greatpriority in the last years, according to the author's judgment, in order to attend the demands of the public educational system, specifically at a basic level coherently and rationally.